Observation Strategy and Flight Configuration for Monitoring Earth Dynamics with the Tandem-L Mission - Tridon, Daniela Borla; Sica, Francescopaolo; De Zan, Francesco; Bachmann, Markus; Krieger, Gerhard (IEEE International Geoscience and Remote Sensing Symposium (IGARSS), 2018)
Tandem-L is a proposal for a spaceborne L-band SAR mission for the systematic observation of dynamic processes on the Earth's surface with hitherto unparalleled quality and resolution. The enormous amount of data to be acquired will be used to provide information concerning dynamic processes in the biosphere, geosphere, cryosphere, and hydrosphere [1]. Within the scope of this mission, several operational phases have been established and corresponding flight configurations have been designed. Subsequently an observation concept has been developed in order to fulfill all the scientific requirements. A sophisticated planning and optimization process has been implemented. It combines the predetermined satellite resources, ground station network, and the scientific requirements to generate an acquisition timeline on individual data take level. The resulting timeline fulfills all requirements for the various scientific applications and can be used to analyze different aspects of the mission like data volumes and orbit usage.
Keywords: Observation Strategy; Tandem-L